Development and validation of the Chinese social media addiction scale. (1st November 2018) - Liu, Chang; Ma, Jianling
Abstract: Accumulating evidence has shown that social media addiction is a growing problem in China, especially among emerging adults. Nonetheless, the absence of a psychometrically sound measuring tool obstructs further progress in this field. Therefore, we examined the properties of a newly developed social media addiction scale among a sample of 619 college students. An exploratory factor analysis revealed that the scale had six factors: preference for online social interaction, mood alteration, negative consequence and continued use, compulsive use and withdrawal, salience, and relapse, which explained 63.83% of the total variance. Cronbach's alpha and half-split coefficient of the whole scale were 0.937 and 0.879, respectively. A confirmatory factor analysis indicated that the six-factor model was a good fit to the data. Moreover, the social media addiction scores were positively correlated with smartphone addiction, pathological Internet use, and narcissism, but negatively associated with self-esteem. Our study suggests that the newly developed social media addiction scale could be used as an effective tool to assess social media addiction among emerging adults in China. Highlights: Social media addiction is a growing problem in China among emerging adults We developed a social media addiction scale for college students We examined the psychometric properties of the scale; it was reliable and valid An EFA revealed six factors, explaining 63.83% of the total variance A CFA indicate that the six-factor model was a good fit to data